Exploring Lipoprotein-Associated Phospholipase A2 Levels in Iraqi Patients with Stable Angina: Insights from Coronary Angiography Diagnosis - Aseel Ghassan Daoud; Wassan Abdul Kareem Abbas; Ahmed Yousif Hasan; Maha N. Abu Hajleh (Al-Mustansiriyah Journal of Pharmaceutical Sciences)
Stable angina is a prevalent heart disease which can be defined as a clinical syndrome of stable coronary artery disease (CAD) that refers to the presence of myocardial ischemia. Lipoprotein-associated Phospholipase A2 (Lp-PLA2) is an important biomarker of atherosclerosis progression through pro-inflammatory and anti-inflammatory effects.